2014
DOI: 10.1589/jpts.26.1883
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Stroke Patients’ Gait Parameters with Fear of Falling

Abstract: [Purpose] The purpose of this study was to assess the correlation of gait parameters with fear of falling in stroke survivors. [Subjects] In total, 12 patients with stroke participated. [Methods] The subjects performed on a Biodex Gait Trainer 2 for 5 min to evaluate characteristic gait parameters. The kinematic gait parameters measured were gait speed, step cycle, step length, and time on each foot (step symmetry). All the subjects also completed a fall anxiety survey. [Results] Correlations between gait para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…Few studies have evaluated the relationship between fear of falling and step length in stroke. Park et al showed that fear of falling was related to step cycle while walking but not to step length in only 12 stroke subjects, which contrasts with the present results [ 43 ]. However, many studies in elderly subjects have also demonstrated a relationship between fear of falling and decreased step length [ 44 , 45 , 46 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Few studies have evaluated the relationship between fear of falling and step length in stroke. Park et al showed that fear of falling was related to step cycle while walking but not to step length in only 12 stroke subjects, which contrasts with the present results [ 43 ]. However, many studies in elderly subjects have also demonstrated a relationship between fear of falling and decreased step length [ 44 , 45 , 46 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In a few studies using a treadmill, speed-increase training has been considered a beneficial approach for improving the gait speed on ground to a greater extent than traditional programs that train at slower speeds in patients with stroke16,17,18 ) . Some stroke patients are afraid of falling because of gait and balance impairments19 ) . In addition to the assistive function of the HAL device described above, a walking device (All-In-One Walking Trainer) with a harness would enable performance of high-speed gait training without the risk of falling.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the kinematic differences between participants may be attributed to the effects of walking at a slower speed. Walking at a slower than normal speed has been shown to result in a decrease in peak knee flexion (Kirtley, 2006, Kwon et al, 2014, and is a common characteristic of gait for older adults or stroke survivors who fear they may be at risk for falling (Park andYoo, 2014, Maki, 1997). In this study, participants walked at a selfselected speed, and non-trippers walked faster than trippers (P < .001).…”
Section: Limitationsmentioning
confidence: 99%